EVAPORATIVE COOLING TECHNOLOGY TO PROLONG SHELF LIFE STORAGE OF FRESH FRUITS AND VEGETABLE - Mhd. Iqbal Nusa (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
Evaporative cooling technology could have used to phostharvest handling fresh fruits and vegetables. This piper explain about; the principle cooling, classification and type of evaporative cooler have used for prolongs shelf life of fresh fruits and vegetables, a design process of evaporative cooler. Main function of evaporative cooler operation was attained to drop temperature and increased relative humidity of storage room cooling. This condition could minimized destroyed rate of material and prolong shelf life as while as down activity enzymatic and respiration. The increasing relative humidity could retarded water losses and gas ethylene activity and production. Handling and low temperature storage was physical method available to controle losses of pascapanen products. An applications of low cost storage system was principle of evaporative cooling in storage of fruits and vegetable. Evaporative cooling as physical fenomenon where moisture evaporate at wet material surface to ambient atmosfer interface it other, so moist material temperature was drop namely cooling process. Dry bulb temperature and wet bulb temperature difference of air in let and out let system was result of evaporative cooling did. Evaporative cooler designed was system of componens namely shielve and room cooling (cabinet), cooling fan, and cooling pad.Key word: evaporative cooling, cooling pad, prolong shelf life storage fruits and vegetables